PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR IPS PADA PESERTA DIDIK KELAS V SDN 03 TIUMANG KABUPATEN DHARMASRAYA - Visi Ofi Utami (Universitas Pendidikan Ganesha, 2022)
The implementation of one of the learning models that can affect students is the Problem Based Learning (PBL) model. This model presents a real problem for students as the beginning of learning. This study aims to determine the effect of the Problem Based Learning (PBL) model on social studies learning outcomes for fifth grade students at SDN 03 Tiumang, Dharmasraya Regency. This research is classified into quantitative research. The research design used by the author is a Quasi Experimental Design in the form of Posttest Only Control Design. The subjects in this study were all fifth grade students at SDN 03 Tiumang. Then calculated using a simple paired t-test. Based on the results of the paired sample t test, it is known that the significant (2-tailed) value is 0.141>0.05, then Ho is rejected and Ha is accepte, it can be concluded that Ho is rejected and Ha is accepted, so it means that there is an effect of the Problem Based Learning (PBL) model on social studies learning outcomes for fifth grade students at SDN 03 Tiumang, Dharmasraya Regency.